2013
DOI: 10.1016/j.taap.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative developmental toxicity of environmentally relevant oxygenated PAHs

Abstract: Oxygenated polycyclic aromatic hydrocarbons (OPAHs) are byproducts of combustion and photo-oxidation of parent PAHs. OPAHs are widely present in the environment and pose an unknown hazard to human health. The developing zebrafish was used to evaluate a structurally diverse set of 38 OPAHs for malformation induction, gene expression changes and mitochondrial function. Zebrafish embryos were exposed from 6 to 120 h post fertilization (hpf) to a dilution series of 38 different OPAHs and evaluated for 22 developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
148
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(168 citation statements)
references
References 59 publications
(76 reference statements)
18
148
2
Order By: Relevance
“…However, recent experimental studies show that several oxidized PAHs could remain particle-bound, and often appear as higher molecular weight peaks in particle mass spectra (25,39). Some oxidized BaP species have been shown to be toxic (40), and some are direct-acting mutagens (39); therefore, it is important to quantify their atmospheric exposure. Here, we track the oxidation Global and regional population-weighted ILCR for PAH mixtures calculated for the default unshielded (red) and new shielded (blue) modeling formulations using 0.1°× 0.1°downscaled BaP concentrations, as described in SI Appendix.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent experimental studies show that several oxidized PAHs could remain particle-bound, and often appear as higher molecular weight peaks in particle mass spectra (25,39). Some oxidized BaP species have been shown to be toxic (40), and some are direct-acting mutagens (39); therefore, it is important to quantify their atmospheric exposure. Here, we track the oxidation Global and regional population-weighted ILCR for PAH mixtures calculated for the default unshielded (red) and new shielded (blue) modeling formulations using 0.1°× 0.1°downscaled BaP concentrations, as described in SI Appendix.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to direct mutagenicity and carcinogenicity [4,5], in vivo assays have shown that quinones are highly redox active, cascading the formation of reactive oxygen species (ROS) within the cell [6]. The presence of ROS can cause severe oxidative stress within cells [7] and lead to the development of diseases and pathological conditions such as asthma, cardiovascular diseases, Alzheimer, diabetes, or cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that after contamination, PAHs are preferentially localized in the mitochondria (Zhu et al, 1995). Moreover, a decrease in mitochondrial O 2 consumption rate has been observed in zebrafish after exposure to a cocktail of PAHs (Knecht et al, 2013). In this study, the permeabilization of cells using saponin made possible to analyze functional mitochondria in situ, in their normal intracellular position, and the use of selected substrates and inhibitors allowed the analysis of different elements of the respiratory chain.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, these highly reactive products are known to have a negative impact on complexes I, III and IV of the respiratory chain (Musatov and Robinson, 2012). If, petroleum compounds are known to induce mitochondrial alteration (Zhu et al, 1995;Knecht et al, 2013), dispersants could also have the same mechanism of action. They appear to stimulate ROS production: a study of Milinkovitch et al (2013) has shown increased antioxidant defenses in the hearts of Liza aurata exposed to Finasol OSR 62.…”
Section: Discussionmentioning
confidence: 99%